(untitled) (Al-Aasar, 2025)
This research article provides an in-depth analytical study of the intersection between spirituality and psychological therapy through the lens of Sufism. In contemporary societies, mental health challenges such as stress, anxiety, and depression are increasingly prevalent, yet conventional psychological approaches often focus primarily on symptom management, overlooking the deeper existential and spiritual dimensions of human experience. This study argues that Sufi spiritual practices, including dhikr (remembrance of God), muraqabah (meditation), and muhasabah (self-accountability), can complement modern psychological interventions to produce a more holistic approach to mental well-being. The article begins by exploring the historical and philosophical background of spiritual healing, highlighting how ancient civilizations integrated spiritual practices into therapeutic processes. In Islamic tradition, particularly within Sufi teachings, the human being is understood as a composite of body, nafs (self), and ruh (soul). While physical ailments are treated through medicine, psychological disturbances are addressed through self-discipline and moral training, and spiritual ailments are alleviated through a connection with the Divine. Prominent Sufi scholars, such as Hazrat Ali Hujwiri (Kashf al-Mahjub) and Shah Waliullah Dehlawi (Hujjatullah al-Baligha), emphasized the significance of self-purification and spiritual practices as a means of addressing both psychological and existential disturbances, offering an integrative framework that resonates with contemporary holistic therapy approaches. The study further examines the parallels and distinctions between modern psychological frameworks and Sufi spiritual practices. While modern psychology, including cognitive-behavioral and positive psychology approaches, emphasizes symptom reduction and behavioral modification, Sufi practices focus on inner transformation, moral development, and alignment with higher spiritual values. Despite these differences, both approaches converge on the goal of enhancing human well-being, self-awareness, and emotional balance. Incorporating Sufi practices into psychological therapy can therefore strengthen resilience, improve emotional regulation, and foster a sense of purpose and meaning in life, aspects often overlooked in conventional therapy. Additionally, the research highlights the social and ethical dimensions of Sufi spiritual practices. Participation in communal spiritual exercises, such as group dhikr or Sama‘(spiritual listening), cultivates empathy, social cohesion, and interpersonal harmony. Such communal engagement provides a supportive environment that enhances psychological recovery and promotes social well-being. The integrative model proposed in this study suggests that addressing both individual and collective dimensions of human experience is essential for sustainable mental health outcomes. In conclusion, this research demonstrates that combining Sufi spiritual practices with contemporary psychological therapy offers a comprehensive, multidimensional model for mental health and personal development. This integrative approach not only addresses immediate psychological symptoms but also fosters long-term spiritual growth, ethical awareness, and social harmony. The study contributes to the growing discourse on holistic therapy by providing empirical, historical, and theoretical support for the inclusion of spiritual dimensions in psychological practice. It advocates for the development of culturally sensitive and spiritually informed therapeutic interventions that can effectively meet the needs of diverse populations in modern societies.